The The Barriers in Online Assessment for Professional Certification: A Case Study In Indonesia - Citra Manggalasari, Lena; Jantos, Anne; Koehler, Thomas; Yuliastuti, Yuliastuti; Wijayanti, Yureana; Setyandito, Oki; Sutarto, Sutarto; Wisni Septiarti, Serafin (LPPM Undiksha, 2023)
Certification exams conducted online must be of the same quality as those conducted on-site. To achieve this, it is necessary to conduct a study in which assessors need to identify obstacles in implementing online certification examinations which have been implemented during the Covid-19 pandemic. The study aims to analyze the perspective of the assessors to identify the barrier factors, understand the interrelation among them, and propose improvements to the online application process. The method applied was the MICMAC (Matrix of Cross-impact Multiplications Applied to Classification), a structural model, to analyze the variables based on their influence and dependence driving force. A case study was conducted on the Indonesia Hydraulic Engineer Association. The data was collected from a focus-group discussion with the assessors. The result revealed that the barrier factors consist of technical aspects, such as internet connection delay, hackers and viruses, and unverified e-document; and social aspects, such as questioning skills limitation, non-verbal communication skills limitation, and environment distraction. The study found that internet connection delay and questioning skill limitations are the barriers with the highest influence beyond other barriers in the online assessment process. Also, the questioning skills limitation factor has the highest dependency on other barriers. Hence, it can be proposed that the curricula of the assessors’ training and/or certification program, should be incorporated with the questioning skill in an online assessment environment.